Expanded TOE Framework in E-Commerce Adoption Quality: Can SMEs in Indonesia Achieve Business Sustainability? - Yoga Religia; Yussi Ramawati; Muafi Muafi (Universitas Islam Nahdlatul Ulama Jepara, 2026)
Objective: This study aims to extend the Technology–Organization–Environment (TOE) framework by integrating e-commerce adoption quality as a mediating mechanism influencing SME business sustainability in Indonesia. Research Design & Methods: A quantitative approach was employed using survey data from 186 Indonesian SMEs operating in Yogyakarta, West Java, and Jakarta. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test both direct and mediating relationships among TOE dimensions, e-commerce adoption quality, and business sustainability. Findings: The findings indicate that technological, organizational, and environmental contexts significantly and positively influence e-commerce adoption quality. Moreover, e-commerce adoption quality has a direct positive effect on SME business sustainability and fully mediates the relationship between TOE dimensions and sustainability outcomes. Theoretical/Research Implications: This study refines the TOE framework by repositioning it as a strategic model that links adoption determinants with long-term sustainability outcomes. Practical Implications: Policymakers and SME-support institutions should strengthen internal readiness and external environmental support. Social Implications: High-quality e-commerce adoption contributes to income stability and job creation. Contribution and Value Added: This research advances TOE-based adoption literature by incorporating e-commerce adoption quality and business sustainability.